2007
DOI: 10.1038/sj.jid.5700919
|View full text |Cite
|
Sign up to set email alerts
|

BAFF Antagonist Attenuates the Development of Skin Fibrosis in Tight-Skin Mice

Abstract: The tight-skin (TSK/+) mouse, a genetic model for systemic sclerosis (SSc), develops cutaneous fibrosis and autoimmunity. Although immunological abnormalities have been demonstrated in TSK/+ mice, the roles of B-cell-activating factor belonging to the tumor necrosis factor family (BAFF), a potent B-cell survival factor, have not been investigated. Serum BAFF levels in TSK/+ mice were examined by ELISA. Newborn TSK/+ mice were treated with BAFF antagonist, and then skin fibrosis of 8-week-old mice was assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 61 publications
4
46
0
Order By: Relevance
“…BAFF is mainly secreted by monocytes, dendritic cells, and T cells. (Rahman et al, 2003;Rahman and Manser, 2004;Zhang et al, 2005;Matsushita et al, 2007). BAFF stimulation also results in prolonged survival of mature resting B cells (Do et al, 2000;Gross et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BAFF is mainly secreted by monocytes, dendritic cells, and T cells. (Rahman et al, 2003;Rahman and Manser, 2004;Zhang et al, 2005;Matsushita et al, 2007). BAFF stimulation also results in prolonged survival of mature resting B cells (Do et al, 2000;Gross et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…BAFF binds to three receptors, BAFF-R, transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI), and B cell maturation Ag (BCMA) (Rahman et al, 2003;Rahman and Manser, 2004;Zhang et al, 2005;Matsushita et al, 2007;Kim et al, 2009). TACI and BCMA also bind a closely related cytokine, a proliferation-inducing ligand (APRIL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, B cell depletion therapy suppresses the development of skin fibrosis in the tight-skin mouse [3,4]. In addition, several recent studies have revealed a possible beneficial effect of antihuman CD20 antibody (rituximab) therapy for SSc patients [5].…”
mentioning
confidence: 99%
“…This B cell activity was enhanced by B cell activation in the presence of anti-IgM and BAFF [32]. Interestingly, BAFF serum levels are increased in the tight-skin (TSK/+) mouse model and blockade of the BAFF/BAFF-receptor interaction can prevent the development of skin fibrosis, inhibit autoantibody generation, and increase the production of anti-fibrotic cytokines (i.e., IFN-γ) [67]. In a bleomycin-induced model of pulmonary fibrosis, BAFF neutralization or BAFF gene deletion resulted in attenuated fibrosis.…”
Section: B Cells In Ssc and Fibrosismentioning
confidence: 99%